Therapeutic Drug Monitoring of Dalbavancin in Real Life: A Two-Year Experience - Dario Cattaneo; Marta Fusi; Marta Colaneri; Chiara Fusetti; Camilla Genovese; Riccardo Giorgi; Maddalena Matone; Stefania Merli; Francesco Petri; Andrea Gori (MDPI AG, 2023)
Dalbavancin is a long-acting lipoglycopeptide that is registered for the treatment of acute bacterial skin and skin structure infections, and it is also increasingly used for infections that require prolonged antibiotic treatment. Here, we present the results from the first 2 years of a service set up in December 2021 for the therapeutic drug monitoring (TDM) of dalbavancin in clinical settings. In particular, we compared the trough concentration (Cmin) to maximum concentration (Cmax) in patients with osteoarticular infections receiving prolonged treatment with dalbavancin. Log-linear regression models were used to estimate the timing of dalbavancin administration with the goal of maintaining Cmin concentrations of >8 mg/L in the two TDM-based strategies. From December 2021 to November 2023, 366 TDMs of dalbavancin from 81 patients were performed. The Cmin and Cmax concentrations of dalbavancin ranged from 4.1 to 70.5 mg/L and from 74.9 to 995.6 mg/L, respectively. With log-linear regression models, we estimated that each injection should be administered every 42-48 days to maintain the Cmin concentrations. Out of the 81 patients, 37 received at least three doses of dalbavancin for the treatment of osteoarticular infections. Despite there being no significant differences in the days of dalbavancin treatment (130 ± 97 versus 106 ± 102 days), the patients in the Cmax-based TDM group received a significantly lower number of dalbavancin injections (5.2 ± 1.8 versus 7.3 ± 2.6 injections, p = 0.005), and they were administered over a longer period of time (40 ± 10 versus 29 ± 14 days, p = 0.013) than in the Cmin-based TDM group. In conclusion, Cmax-based TDM was associated with a significant reduction in the inter-individual variability of dalbavancin concentrations and lower drug dosing frequency than those of Cmin-based TDM. This approach could, therefore, favor a more rational and targeted use of dalbavancin in patients requiring prolonged treatment.